HFE-Related Hemochromatosis: The Haptoglobin 2-2 Type Has a Significant but Limited Influence on Phenotypic Expression of the Predominant p.C282Y Homozygous Genotype - Gérald Le Gac; Chandran Ka; Isabelle Gourlaouen; Laurence Bryckaert; Anne-Yvonne Mercier; Brigitte Chanu; Virginie Scotet; Claude Férec (Advances in Hematology)
Phenotypic expression of the common p.C282Y/p.C282Y HFE-related hemochromatosis genotype is heterogeneous and depends on a complex interplay of genetic and non-genetic factors. Haptoglobin has a crucial role in free hemoglobin iron recovery, and exists as three major types: Hp1-1, Hp2-1 and Hp2-2. Hp2-2 favors endocytosis of hemoglobin iron in monocytes/macrophages, resulting in partial iron retention and increased intracellular ferritin levels. This situation is generally not expected to severely affect iron homeostasis, but was found to correlate with elevated serum iron indices in healthy men. Whether the Hp2-2 genotype acts as a modifier in HFE-related hemochromatosis is unclear. In this study we investigated influence of Hp2-2 and of potential confounders on the iron indices of 351 p.C282Y homozygous patients. We conclude that there is a cause-and-effect relationship between the Hp2-2 genotype and increased iron indices in p.C282Y homozygous patients. The Hp2-2 effect is, however, limited and only apparent in males.